Experience of Bullying Behavior in Students as Witnesses (Bystander/Upstander) Students in South Jakarta City - Wahyuniar, Lely; Iman Pustakasari, Endahing Noor (Annpublisher, 2025)
Background. Often, the case of bullying incidents goes viral, thanks to children who witness bullying incidents acting as bystanders/upstanders. This role is dilemmatic; if you are passive, you feel psychologically distressed because you are faced with a situation and are at risk of becoming a victim. However, there are also those who dare to stop bullying incidents by defending the victim as a form of high empathy, good social skills, and a sense of moral responsibility. Upstanders face risks such as being targeted for revenge or social pressure from the perpetrator. Therefore, it is necessary to gain the attention of stakeholders. Purpose. This study aims to investigate the behavior of students as witnesses, both as bystanders and upstanders, in bullying cases in the city of South Jakarta. Method. This research method uses a quantitative approach, a type of descriptive research. The data analysis techniques employed include descriptive statistics, validity, and reliability. Data analysis is processed using IBM SPSS and Python. Result. In terms of the bystander/upstander aspect, almost all respondents reported experiencing bullying incidents (M = 0.99; SD = 0.07), and most had an understanding of the appropriate course of action to take (M = 0.88; SD = 0.33). Respondents were also relatively familiar with the existence of the upstander (M = 1.26; SD = 0.77), albeit with considerable variation. Students' assessment of the school's success rate in handling bullying cases was relatively good (M = 2.79; SD = 0.96), while students' knowledge related to school anti-bullying policies was also relatively high (M = 0.78; SD = 0.41). Conclusion. Although verbal bullying behavior is still quite prevalent, most students have the awareness to act as bystanders or upstanders. However, there are still respondents who are passive when they see bullying, but some others have also played a role as helpers. With the active involvement of students and all stakeholders, it is hoped that efforts to prevent and address bullying in schools, especially at the junior high school/high school levels, can be implemented more effectively, creating a safe and inclusive learning environment that supports the positive development of students' character. Implementation. Teachers and school counselors are expected to provide regular education about the impact of bullying and foster a school culture that encourages students to take a stand against it